Survivors of Climate Driven Abalone Mass Mortality Exhibit Declines in Health and Reproduction Following Kelp Forest Collapse - Rogers-Bennett, Laura; Klamt, Robert; Catton, Cynthia A. (Frontiers in Marine Science, 2021)
Marine ecosystems are vulnerable to climate driven impacts events such as marine heatwaves yet we have a poor understanding of whether they will collapse or recover. Kelp forests are known to be susceptible, and there has been a rise in sea urchin barrens around the world. When temperatures increase so does physiologic physiological demands while food resources decline, tightening metabolic constraints. In this case study, we examine red abalone (Haliotis rufescens ) looking at sublethal impacts and their prospects for recovery within kelp forests that have shifted to sea urchin barrens. Abalone are a recreationally fished species that once thrived in northern California’s bull kelp forests but have recently suffered mass mortalities since the 2014-2016 marine heatwave. Quantitative data exist on the health and reproduction of abalone both prior to and after the collapse. The survivors of the mass mortality show a two-year lag in body and gonad condition indices. After the lag, body and gonad indexes decreased substantially, as did the relationship between shell length and body weight. Production of mature eggs per female declined by 99% (pp<0.001), and the number of eggs per gram of female body weight (2984/gm) declined to near zero (9/gm). The number of males with sperm was reduced by 33%, and the sperm abundance score was reduced by 28% (p=0.414). We observed that these reductions were for mature eggs and sperm while immature eggs and spermatids were still present in large numbers. In the lab, after reintroduction of kelp, 50% of the starved abalone died and weight gains were quickly lost following a second starvation period. This example illustrates how climate-driven declines in foundation species can suppress recovery of the system by impacting body condition and future reproduction of surviving individuals. Given the poor reproductive potential of the remaining abalone in northern California, coupled with ongoing mortality and low kelp abundances, we discuss the need to maintain the fishing moratorium and implement active abalone restoration measures. For fished species, such as abalone, this additional hurdle to recovery imposed by changes in climate is critical to understand and incorporate into resource management and restoration.